IL-7-Adjuvanted Vaginal Vaccine Elicits Strong Mucosal Immune Responses in Non-Human Primates - Logerot, Sandrine; Figueiredo-Morgado, Suzanne; Charmeteau-de-Muylder, Bénédicte; Sandouk, Abdelkader; Drillet-Dangeard, Anne-Sophie; Bomsel, Morgane; Bourgault-Villada, Isabelle; Couëdel-Courteille, Anne; Cheynier, Rémi; Rancez, Magali (Frontiers in Immunology, 2021)
Mucosal immune responses are crucial in protecting against pathogens entering through mucosal surfaces. However, due to poor T-cell responsiveness upon mucosal antigenic stimulation, mucosal immunity remains difficult to obtain through vaccines and requires appropriate adjuvants. We previously demonstrated that administered systemically to healthy macaques or locally expressed in the intestinal mucosa of acutely SIV-infected macaques, interleukin-7 (IL-7) triggers chemokine expression and immune cell homing into mucosae, suggesting its important role in the development of mucosal immune responses. We therefore examined whether local delivery of recombinant glycosylated simian IL-7 (rs-IL-7gly) to the vaginal mucosa of rhesus macaques could prepare the lower female genital tract (FGT) for subsequent immunization and act as an efficient mucosal adjuvant. First, we showed that local administration of rs-IL-7gly triggers vaginal overexpression of chemokines and infiltration of mDCs, macrophages, NKs, B- and T-cells in the lamina propria while MamuLa-DR+ APCs accumulated in the epithelium. Subsequent mucosal anti-DT immunization in macaques resulted in a faster, stronger, and more persistent mucosal antibody response compared to DT-immunization alone. Indeed, we detected robust productions of DT-specific IgAs and IgGs in their vaginal secretions and identified cells secreting DT-specific IgAs in their vaginal mucosa and IgGs in draining lymph nodes. Finally, the expression of chemokines involved in the organization of tertiary lymphoid structures (TLS) was only increased in the vaginal mucosa of IL-7-adjuvanted immunized macaques. Interestingly, TLSs developed around PNAd+ high endothelial venules in their lower FGT sampled 2 weeks after the last immunization. Non-traumatic vaginal administration of rs-IL-7gly prepares the mucosa to respond to subsequent local immunization and allows the development of a strong mucosal immune response in macaques, through the chemokine-dependent recruitment of immune cells, the activation of mDCs and the formation of TLSs. The localization of DT-specific IgA+ plasma cells in the upper vaginal mucosa argues for their contribution to the production of specific immunoglobulins in the vaginal secretions. Our results highlight the potential of IL-7 as a potent mucosal adjuvant to stimulate the FGT immune system and elicit vaginal antibody responses to local immunization, which is the most promising way to confer protection against many sexually transmitted diseases.